Reassessing the Role of Anthropogenic Climate Change in the Extinction of Silphium - Pollaro, Paul; Robertson, Paul (Frontiers in Conservation Science, 2022)
The famed ancient herb, known to the Romans as silphium (Greek silphion), is widely regarded as the first recorded instance of human-induced species extinction. Modern scholars have largely credited direct exploitation (e.g. over-harvesting; over-grazing) as the primary cause of silphium’s extinction, due to an overwhelming demand for the plant in ancient times. Recent research has revealed strict cold-stratification requirements for the germination of silphium’s closest living relatives, revealing the likelihood that silphium shared these same germination requirements. Documented environmental changes in ancient Cyrenaica (widespread deforestation; cropland expansion) likely resulted in accelerated rates of desertification throughout the region as well as the direct disturbance of silphium’s habitat, effectively eliminating the necessary conditions for silphium’s successful germination and growth within its native range. Contrary to previous conclusions, this evidence suggests that anthropogenic environmental change was instead the dominant factor in silphium’s extinction, marking silphium as the first recorded instance of human-induced microclimatic extinction.